Peran Facebook dalam Kampanye Politik Pemilukada di Kabupaten Ogan Kemiring Ulu - Hendra Alfani (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
Facebook, one of social media, becomes a new space for everyone to interact and socialize without being limited by space and time, like in conventional media (mainstream). In its development, social media is also used to support political campaign in general election of regional head (Pemilukada). In addition to reaching the audience without being limited space and time, the cost is also cheap and efficient. Facebook has been chosen by candidates for regional heads as a medium of communication and socialization, not just relying on television media, advertisements in newspapers, banners, billboards, and other media. Candidates also take advantage of social media technology through facebook with the aim to provide access to information for public through cyberspace. The use of facebook is also done by the pair of candidates in the regional head election of Ogan Komering Ulu (OKU) South Sumatra Province in 2015. This study found the use of facebook is quite significant by both pairs of candidates in the election OKU in order socialization and political campaign.